Combination of PCR analysis and sequencing on cytochrome-b gene Canis lupus familiaris for halal authentication - Kurniasih, Kholif Sholehah Indra; Erwanto, Yuny (Journal of Halal Science and Research, 2023)
The adulteration of beef with lower-priced meat, such as dog meat, is common to get economic profit. Dog meat is one type of meat that is not halal for consumption. There are several ways in which beef can be adulterated, including the use of dog meat. Specific primers for cytochrome-b (CYTBCA3-kh) can be used to identify the presence of dog meat contamination. This study aimed to identify dog meat using these primers. After conducting conventional PCR and agarose electrophoresis tests, the specificity of the primers was confirmed. Following this, the DNA base sequence was analyzed using a sequencing method to ensure accurate identification of dog meat contamination in beef. Specific dog primers tested on cattle, pigs, wild boars, goats, chickens, rabbits, and rats were confirmed using conventional PCR and agarose gel electrophoresis. Amplicon length verification was analyzed in a silico sequencing method using MUSCLE and BLAST NCBI software. The results showed that the primer CYTBCA3-kh amplified the canine Cyt-b mt-DNA gene specifically. The amplicon length obtained was 111 base pairs (bp), with a similarity value of 99.12% with Canis lupus familiaris mitochondrion, complete genome. The specific primer CYTBCA3-kh can be used to identify dog ​​meat contamination in meatball products for halal authentication. Keywords: CYTB gene, Halal Authentication, PCR, Sequencing, Canis lupus familiaris